“Diseño y construcción de un exoesqueleto para las extremidades inferiores de infantes con discapacidad motriz”. - Guamangate Tipán, Cristian Ricardo (2022)
This degree work presents the design and building of a prototype of an exoskeleton for the lower extremities of people with motor disabilities, where a biomechanical sketch is built with a mechanical distribution that is configured to the conditions and dimensions of the person evaluated, a bibliographic research was carried out to obtain relevant information about human anthropometry, the selection of electrical and electronic materials was developed, from which the use of direct current motors that have a capacity to handle up to 100 pounds force, a speed reducer to stabilize the operating torque can be downloaded. The exoskeleton was designed for heights from 110 to 139 centimeters, equivalent to infants from 6 years to 11 years and a maximum weight of 35 kg, the tests were carried out in two children with 1 and 2 degrees of disability, respectively, with thin builds, therefore, Padded type bras were adjusted to the needs of the infants, with respect to the height of the support structure, it had to be decreased a few centimeters to adjust the comfort of the patient. The prototype was adjusted in a good way with this infant who presents a grade 1 and 2 disability.